PENGEMBANGAN PRODUK DAUN KELOR MELALUI FORTIFIKASI DALAM UPAYA PENANGANAN STUNTING - Selpina Embuai; Moomina Siauta (Lembaga Penerbitan Fakultas Kesehatan Universitas Kristen Indonesia Maluku, 2020)
ABSTRACTBackground: Stunting is a condition where toddlers whose height for age is below the standard. Toddlers who have low body weight based on age are caused by insufficient intake of nutrients in the long term. Stunting can have a negative impact on cognitive and motor development and increase the risk of overnutrition, non-communicable diseases and reduce productivity in adulthood. The prevalence of stunting in the world in under-fives in 2020 has decreased significantly by 22% (4). The results of the 2018 Basic Health Research (Riskesdas) show that the prevalence of stunting in children under five in Indonesia has decreased by 6.4% from 37.2% (in 2013) to 30.8%. Various efforts have been made by the government to prevent and overcome stunting. One of them is by using Moringa leaves. Moringa is called the most economical plant and contains very good nutritional value so that it can be used as an alternative in overcoming nutritional problems. In addition, the use of Moringa can be used as biscuits which of course can be used as additional food for toddlersPurpose: Describing evidence based (review of facts) in the form of a literature review on Moringa Leaf Product Development Through Nutrification in the Handling of StuntingMethod:The method used in this Literature review begins with selecting a topic, then determining keywords to search for journals using English and Indonesian through several databases, including Google Scholar, Ebscho, Pro Quest, and journal of nursing science. This search is limited to journals from 2011 to 2021. The English keywords used are “Moringa Leaves and Stunting”. For Indonesian use the keywords